Impact of Crush Zone on PPV in Claystone and Limestone Blasting with a Quantitative Approach - Noveriady Noveriady; Devin Tesario Grunadi; Neny Fidayanti (Universitas Islam Raden Rahmat, Malang, 2026)
Blasting in open pit mines aims not only to achieve optimal rock fragmentation but also to control the impact of generated ground vibration. This study aims to analyze the influence of the crush zone on Peak Particle Velocity (PPV) in blasting activities involving claystone and limestone layers. Field data were collected from 25 blasting operations with varied parameters: number of blast holes 25–160, explosive charge per hole 50–111 kg, and measurement distance 504–537 m. The recorded actual PPV ranged from 1.221 to 3.404 mm/s. Statistical analysis was performed using power regression to model the relationship between Scaled Distance and PPV. The results show a strong inverse relationship between Scaled Distance and PPV, where higher blasting energy concentration forms a more intensive crush zone as the initial source of vibration. Blasting in limestone yields relatively higher PPV compared to claystone under similar Scaled Distance conditions, due to the elastic and more brittle properties of limestone. The model's prediction accuracy reached 91.5% on average. Practically, to maintain PPV at a safe level (<3.404 mm/s), it is recommended to keep the Scaled Distance ≥ 48.82 m/kg⁰·⁵ and limit the explosive charge per hole to the range of 50–90 kg, especially in limestone. This study confirms the key role of the crush zone and rock lithology in blasting vibration mechanisms, providing a basis for optimizing safe and sustainable blasting designs.